MEKANISME PURCHASING SECTION DALAM PENGADAAN BARANG DAILY MARKET LIST DI HOTEL PANGERAN BEACH PADANG - Firiana, Indah; ', Etika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
One of the hotel's revenues is the sale of food at the hotel, which of course cannot be separated from the party responsible for production, which is called Food and beverage product. At Pangeran Beach Padang Hotel, the purchasing section must always ensure that the goods ordered are of high quality. The study aims to determine the mechanism of the purchasing section in the procurement of daily market list kitchen goods at Pangeran Beach Hotel Padang and to find out the obstacles experienced by the purchasing section in the procurement of daily market list kitchen goods. With qualitative descriptive method. By using 3 samples of sources, namely purchasing staff, receiving staff, food and beverage product admin and chef. Data collection techniques in this study were interviews, observation, and documentation. Requests for goods are made in the hotel system, namely power pro. Suppliers do not use a contract system. Goods that arrive will be checked by receiving whether they are in accordance with the PO after that the goods will be stored in the kitchen storage. Keyword : Mekanism, Market List, Purchasing, Hotel